Effects of site preparation methods on soil physical characteristics. - Jusoff, Kamaruzaman; Nik Ab. Majid, Nik Muhamad (1988)
Partially mechanized site preparation for reforestation is common in the humid tropics even though little attention has been given to defining and solving soil problems that may be created. This paper evaluates two site preparation methods (slash and burn and bulldozer clearing with a straight blade) on soil physical properties. Soil pyhsical properties were measured before site preparation and one month after. Compaction increased bulk density and penetrometer resistance of the 0 to 15 cm soil depth for both site preparation meyhods but the increase was significantly higher for the bulldozer prepared treatment. Gravimetric water content at soil matric potentials below 0 kPa was greater for the bulldozer prepared soil. The infiltration rate 1 month after site preparation decreased 30 and 80 percent for soil prepared by slash and bulldozer, respectively, as compared to initial conditions. Detrimental changes in soil pyhsical properties caused by site preparation suggest the need of post management practices such as bedding and fertilization.